Local gentamicin application does not interfere with bone healing in a rat model - Fassbender, Marion; Minkwitz, Susann; Kronbach, Zienab; Strobel, Catrin; Kadow-Romacker, Anke; Schmidmaier, Gerhard; Wildemann, Britt (Bone, 2013)
For the prophylaxis and treatment of bony infections antibiotics are locally used. Since several decades antibiotics mixed with bone cement (methylmethacrylate) are successfully used in prosthetic surgery and a gentamicin coated tibial nail is approved in Europe for fracture stabilization. The goal of the present study was to investigate if gentamicin, locally applied from a polymeric coating of intramedullary nails, might interfere with the bone healing process. Female Sprague Dawley rats (n=72) were used and the tibiae were intramedullary stabilized with Kirschner-wires (k-wires) after osteotomy. This model was established earlier and shows a delayed healing with a prolonged inflammatory reaction. The open approach is clinically more relevant compared to a closed one because it mimics the clinically critical case of an open fracture, which has a higher risk of infection. The k-wire was either coated with the polymer poly(D,L-lactide) (control group) or with 10 % gentamicin incorporated into the polymer (gentamicin group). In vivo μCT analyses were performed at days 10, 28, 42, and 84 after osteotomy. Mechanical torsional testing and histological evaluation were done at the days of sacrifice: 28, 42, and 84. The μCT analyses revealed an increase in tissue mineral density (TMD) over the healing period in both groups. In the control group, the torsional stiffness and maximum load did not reach the values of the intact contralateral side at any time point. At day 84 the gentamicin treated tibiae, however, showed significantly better maximum load compared to the control group. The histology showed no bony bridging in the control, whereas in 2 of 5 calluses of the gentamicin group mineralized bridging occurred. Significantly more mineralized tissue was measured in the gentamicin group. This study shows that the local gentamicin application does not negatively interfere with the long term healing process. Local infection prophylaxis is effective without negative effects on bone healing.
Gesehen am 04.03.2021